Manajemen Kualitas Pangan Dalam Perspektif Jaminan Halal - Silvia Br Nainggolan; Chuzaimah Batubara (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to analyze the quality management of food with a focus on halal assurance aspects. Halal assurance is crucial in the food industry to ensure compliance with halal principles throughout the supply chain, from production to consumption. In this research, the author explores how quality management systems are applied to ensure food products are safe, halal, and in accordance with established standards. The research method used in this study includes a qualitative approach. Qualitative research involves in-depth analysis of the practices of food quality management and halal assurance attempted by food producers, food authorities, and the perceptions and beliefs of consumers related to halal. The research findings demonstrate that effective food quality management heavily relies on the implementation of a strict halal assurance system. Successful food producers who adopt comprehensive halal standards in all creation and distribution processes gain a competitive advantage by attracting more consumers from the growing halal market. This research provides valuable insights for the food industry to continuously innovate and ensure that the produced food is halal, safe, and of high quality.